16.4k views
3 votes
Solve the following system:
y=1
y=-6x-5

2 Answers

0 votes
1= -6x-5
+5. +5
6=-6x
/-6. /-6

x=-1
User Vinnie Fusca
by
4.9k points
4 votes

Answer:

x = -1

y = 1

Explanation:

Since it gives you "y", plug in the number given into the equation:

y = -6x - 5

1 = -6x - 5

Then, add 5 to both sides:

1 = -6x - 5

+5 + 5

________

6 = -6x

Divide both sides by -6:

6 = -6x

-1 = x

So now you have, x = -1 and y = 1

User Ya Xiao
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.